Diet in Chronic Kidney Disease: an integrated approach to nutritional therapy - Pereira,Raíssa Antunes (2020)
SUMMARY A healthy diet is an essential requirement to promote and preserve health, even in the presence of diseases, such as chronic kidney disease (CKD). In this review, nutritional therapy for CKD will be addressed considering not only the main nutrients such as protein, phosphorus, potassium, and sodium, which require adjustments as a result of changes that accompany the reduction of renal functions, but also the benefits of adopting dietary patterns associated with better outcomes for both preventing and treating CKD. We will also emphasize that these aspects should also be combined with a process of giving new meaning to a healthy diet so that it can be promoted. Finally, we will present the perspective of an integrated approach to the individual with CKD, exploring the importance of considering biological, psychological, social, cultural, and economic aspects. This approach has the potential to contribute to better adherence to treatment, thus improving the patient's quality of life.